A single point mutation engineering for changing the substrate specificity of d-lactate dehydrogenase from Lactobacillus fermentum. (November 2021) - Fan, Xinyu; Bai, Yajun; Fan, Tai-Ping; Zheng, Xiaohui; Cai, Yujie
Abstract: In this study, based on homology modeling and molecular docking, the key residues involved in substrate recognition in the active center of NADH-dependent d -lactate dehydrogenase (LF-d-LDH0653) from Lactobacillus fermentum were analyzed. The site-directed saturation mutagenesis of the key Tyr53 site was carried out to study the substrate specificity of mutants. 19 variants were obtained, of which the most significant change in substrate specificity was observed for variant Y53A. The Michaelis–Menten constant ( K m ), turnover number ( k cat ), and catalytic efficiency ( k cat / K m ) of Y53A to α-ketoisocaproate were 0.13 mM, 112.60 s −1, and 856.67 mM −1  s −1, respectively. The Michaelis–Menten constant ( K m ), turnover number ( k cat ), and catalytic efficiency ( k cat / K m ) of Y53A to phenylpyruvate were 0.16 mM, 78.17 s −1, and 481.62 mM −1  s −1, respectively. The results indicated that Tyr53 was the key site that determines the substrate specificity of the enzyme, and single-point mutagenesis can dramatically affect the catalytic efficiency for various other substrates. Highlights: The key residues affecting substrate specificity of LF-d-LDH0653 were identified. The substrate specificity of LF-d-LDH0653 from Lactobacillus fermentum was changed significantly by mutagenesis. The catalytic mechanisms of mutant were explained.